Risk of Hypertension in People with Poor Sleep Pattern (Study in Puskesmas Tanah Kalikedinding Surabaya) - Shofa Roshifanni (Jurnal Berkala Epidemiologi, 2016)
Hypertension is a non-communicable disease which is a very serious health problem. The prevalence of hypertension in Indonesia is 25.8%. The incidence of hypertension in the Public Health Center (PHC) of Tanah Kalikedinding one year reached 17%. This study aims to analyze the relationship between sleep patterns and the incidence of hypertension and identify risk factors for hypertension in people who have poor sleep patterns at the PHC of Tanah Kalikedinding, Surabaya. This type of research is observational analytic with a case-control design. This research was conducted at the PHC of Tanah Kalikedinding, Surabaya in August 2015 - January 2016. A sample size of 76 people consisted of 38 case samples and 38 control samples. The independent variable studied was the sleep pattern of the respondent while the dependent variable was the incidence of hypertension. Primary data collection was carried out by interview using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while secondary data used the profile of the PHC of Tanah Kalikedinding, Surabaya. Data analysis using Chi-square test. The results showed that there was a significant relationship between respondents' sleep patterns with the incidence of hypertension p = 0,000; OR = 9.02; 95% CI = 2.86 - 29.65), so it is expected that health workers can provide counseling to the public about sleep pattern factors that increase the risk of hypertension such as sleep duration less than the need and poor sleep quality.